The study of the applicability of invar nanostructures for the reduction of p-nitrophenyl compounds - Borgekov, D; Zdorovets, M. V.; Shlimas, D. I.; Kozlovskiy, A. L.; Khlebnikov, N. A.; Kaniukov, E.Yu. (Eurasian Journal of Physics and Functional Materials, 2026)
The results of the study of the phase composition of iron-nickel nanostructures susceptible to electron irradiation on the catalytic reduction of p-nitrophenyl compounds are presented. In the course of the studies, it was found that the nanostructures irradiated with a dose of 250 kGy, which are characterized by the presence of two phases, with the domination of the FeNi phase, have the highest recovery rate. In this case, nanostructures irradiated with a dose of 250 kGy, which showed the highest catalytic reaction rate, have a fairly short lifetime, which may be due to the rapid degradation of the surface of the nanotubes as a result of the interaction of the catalyst with the medium.Recommended CitationBorgekov, D. B.; Zdorovets, M. V.; Shlimas, D. I.; Kozlovskiy, A. L.; Khlebnikov, N. A.; and Kaniukov, E. Yu. (2020) "The study of the applicability of invar nanostructures for the reduction of p-nitrophenyl compounds," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 9.DOI: https://doi.org/10.29317/ejpfm.2020040209